General method of synthesis ultrathin ternary metal chalcogenide nanowires for potential thermoelectric applications. (December 2016) - Zhou, Chongjian; Dun, Chaochao; Wang, Ke; Zhang, Xia; Shi, Zhongqi; Liu, Guiwu; Hewitt, Corey A.; Qiao, Guanjun; Carroll, David L.
Abstract: In this work we demonstrate a solution-based approach to the synthesis of ternary metal chalcogenide nanowires (NWs) with high thermoelectric figure of merit (ZT) and power factors. Utilizing templates of Te1−x Sex alloys to balance the chemical reactivity between Te and Se atoms, we have been able to add a number of different metal species while maintaining a single-phase ternary metal chalcogenide NW with small diameter (<20 nm) and well defined crystal structure. This method opens the door for scalable synthesis ultrathin and composition tunable selenium doped ternary chalcogenide NWs. Moreover, spark plasma sintered NW-based bulk material exhibits ZT value as high as 0.75 which excessed previously nanocrystal and nanoplatelet based one. Examining the temperature dependent behavior of conductivity and Seebeck coefficient, we suggest the charge transfer mechanisms within the system are dominated by the energy barrier between NW-NW nano-junctions. Graphical abstract: We demonstrate a solution-based, catalyst-free approach to the synthesis of ternary metal chalcogenide nanowires utilizing templates of Te1−x Sex . We also show that this is ideal for thermoelectric performance and demonstrate dense nanowire consisted pellet of solution-synthesized ternary metal chalcogenide nanowires with ZT as high as 0.75 and power factors up to 1000 μW m −1  K −2 . Highlights: A general method for synthesis of ternary metal chalcogenide nanowires was proposed. Ultrathin nanowires (<20 nm) were achieved, which are the thinnest so far. Thermoelectric figure of merit as high as 0.75 was obtained by solution-based approach. Energy barrier between nanowire-nanowire heterogeneous junctions was confirmed. Guidelines for improving further thermoelectric were suggested.